Access to planar chiral ferrocenes via N-heterocyclic carbene-catalyzed enantioselective desymmetrization reactions - Lv, Xiaokang (2022)
Ferrocene-derived dicarbaldehydes bearing pro-chiral planes are desymmetrized under the catalysis of chiral N-heterocyclic carbene organic catalysts. The reaction features selective activation and reaction of one of the aldehyde moieties of the ferrocene derivative while leaving the other aldehyde unit untouched. Our reaction affords enantiomerically enriched planar chiral ferrocene products obtained that are amenable for further transformations. Preliminary application studies show encouraging results when our products are explored for catalysis in chemical synthesis and for antimicrobial utilities in pesticide development.